2024
DOI: 10.1002/adma.202311698
|View full text |Cite
|
Sign up to set email alerts
|

High‐Surface Area Mesoporous Sc2O3 with Abundant Oxygen Vacancies as New and Advanced Electrocatalyst for Electrochemical Biomass Valorization

Yufeng Wu,
Liyao Ma,
Junxiu Wu
et al.

Abstract: Scandium oxide (Sc2O3) is considered as omnipotent “Industrial Ajinomoto” and holds promise in catalytic applications. However, rarely little attention have been paid to its electrochemistry. Here, we reported the first nanocasting design of high‐surface area Sc2O3 with abundant oxygen vacancies (mesoporous VO‐Sc2O3) for efficient electrochemical biomass valorization. In the case of the electro‐oxidation of 5‐hydroxymethylfurfural (HMF) to 2,5‐furandicarboxylic acid (FDCA), quantitative HMF conversion, high yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“… Wu et al (2024) reported the first synthesis of mesoporous Sc 2 O 3 electrocatalysts rich in O v via a nano-casting method, enabling the efficient and selective oxidation of HMF to FDCA. This innovation enabled the effective and selective oxidation of HMF to FDCA.…”
Section: Anion Vacancies Promote Hmformentioning
confidence: 99%
“… Wu et al (2024) reported the first synthesis of mesoporous Sc 2 O 3 electrocatalysts rich in O v via a nano-casting method, enabling the efficient and selective oxidation of HMF to FDCA. This innovation enabled the effective and selective oxidation of HMF to FDCA.…”
Section: Anion Vacancies Promote Hmformentioning
confidence: 99%